Inert Gas Axial Flow Analysis on Thermal System with Natural Convection Condition - Rio Anshari; Mairizwan Mairizwan; Fandi Oktasendra; Debi Rianto; Zulhendra Zulhendra (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
The Fukushima nuclear accident in 2011 became the basis for consideration of the use of gas as a coolant in nuclear reactors. This is because the convection rate of gas flow in the cooling channel can occur naturally due to differences in density and does not require the help of a pumps for the circulation of the coolant. This study aims to analyze how the flow pattern of an inert gas on a vertical-axial reference by natural convection in a thermal system. The focus of this research is to study the flow parameters of the coolant with a gas phase. This research is an experimental study. The analysis was carried out using a descriptive approach and computer simulation-assisted numerical analysis methods. The results showed that the distribution and variation of heat was radially dominant in the middle so that the coolant channel wall received less heat load. The magnitude of the pressure drop along the vertical-axial channel shows a homogeneous pattern and decreases radially from center to edge. These results indicate the use of inert gas as a coolant can be considered as an alternative coolant in heat systems that do not depend on pumps in operating conditions.